Motivational characteristics of Sims 4 that can enhance the digital mode of teaching interior design - Mandalones, Lovely Darylene P.
Technological advancements have transformed interior design education, transitioning from traditional methods to utilizing Computer-Aided Design (CAD) programs. This qualitative exploratory research explored the motivational characteristics of Sims 4 that can enhance the digital mode of teaching interior design. There were 21 respondents who were selected through purposive and snowball sampling design, nine of whom were interviewed. The participants chosen are Filipino citizens currently in their third or fourth year in any BS Interior Design program in the Philippines and have been playing Sims 4 for at least a year for its Build Mode features. The findings revealed that the game’s characteristics of being accessible, customizable, and realistic allow individuals to explore their preexisting interest in design, influencing their decision to pursue a degree in interior design. Moreover, it was also revealed that the participants’ perceptions on the digital mode of teaching interior design are generally positive, wherein results showed that the survey respondents viewed the mode to be helpful in their design process and the interview participants viewed it as most helpful in improving their critical thinking and problem-solving skills. interior design can be improved by integrating user-centric approach, gamified learning environment, and real-time design visualization characteristics of Sims 4 into its approaches. The integration of these motivational Sims 4 characteristics has the potential to enhance students’ motivation and learning outcomes within the interior design program. However, potential limitations such as technical requirements must be considered. This study provides a foundation for further research on the enhancement of the digital mode of teaching interior design.